ASPECTS OF PUBLIC SPACE IN THE INFORMAL ECONOMIC SPACES AT LOW-COST APARTMENT BUILDING (RUSUNAWA) IN SURABAYA - Budi Prayitno; Aditha Agung Prakoso; Dedi Hantono; Zubair Butudoka; Danang Yulisaksono (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The human needs for livelihood have become important part as an effort to maintain its survival. Therefore, one of the job opportunities that can be done is to work in the informal sector. The informal sector also appears in public spaces, the example is at low-cost apartment building (rusunawa), such as food stalls and grocery stores in corridors, playgrounds or parking areas of rusunawa. This study looks at the development of the function of the rusunawa as a residence into an informal economic space in the Rusunawa in the City of Surabaya. This study used a qualitative descriptive method, by connecting the correlation between the public space and the informal economy space (logic model analysis and cross-case synthesis). So that it can provide knowledge about the planning and development of rusunawa in the future, as policy guidelines regarding the planning and development of rusunawa. Keywords : Public Space, Informal Economic Space, Affordable Rental Apartments, Surabaya